The Growth of Abalone (Haliotis squamata) In Net Floating Cage At Hulaliu Waters, Central District of Moluccas - M.F Sahetapy, Jacqueline; Latuihamallo, Magdalena (Indonesian Aquaculture Society (MAI), 2014)
Growth of abalone Haliotis squamata were studied over 5 weeks in net floating cages at Hulaliu waters, the Central District of Mollucas. The objectives of the research were to analyze a daily growth rateand absolute growth of abalone Haliotis squamata in net floating cage. A total of 45 abalones were observed, with average initial weight ranged of 8.0-8.5 g. The abalones were treated with 3 types of natural foods, and 3 replications were held. The foods type treatment were using 2 species of macroalga namely Ulva sp., Gracillaria sp. and combination of Ulva sp. and Gracillaria sp.. The water quality was monitored twice a day included water temperature (28.1 – 29.9°C), pH (7-8.5), dissolved oxygen (8.2-10.1 mg/L) and water salinity (29.6-34 ppt). The highest daily growth rate of weight was gained in Ulva sp. treatment which had rate of 0.068 g/day at the fifth week, and also the absolute growth of weight was obtained in Ulva sp. treatment which had rate of 4.0 g in 56 days.